Investigation of Aspiration Pneumonia and Respiratory Tract Complications in Cases Presenting to the Emergency Service with Intoxication: A Prospective Study - DENİZBAŞI ALTINOK, ARZU (EMERGENCY MEDICINE PHYSICIANS ASSOC TURKEY, 2019)
Aim: In this study, we aimed to investigate the frequency of aspiration pneumonia (AP) and factors affecting AP development in patients presenting to the emergency department with intoxication. Materials and Methods: This single-center prospective study was conducted during one year in patients admitted to the emergency service of a tertiary hospital for intoxication within the first two hours. The data obtained during the study were analyzed statistically using the Statistical Package for Social Sciences (SPSS version 22.0). The results were expressed as mean +/- standard deviation. Univariatc statistical analysis was performed using chi-square test for categorical variables and Mann-Whitney U test for non-parametric data. Results: Of the 50 acute poisoning cases included in the study, pneumonia developed in two cases (4%) in the study group within the first seven days and none of the patients in the control group had AP or respiratory complications. No significant difference was found between the study group and the control group in terms of AP development (p=0.113). Conclusion: Based on the results of this study, it was considered that gastric lavage and activated charcoal administration were more closely associated with AP development in patients presenting with intoxication compared other AP risk factors such as age, lower Glascow coma scale, and antidepressant or antipsychotic overdose. Therefore, emergency physicians should be sensitive to such cases in order to reduce the duration of treatment and hospitalization of these patients.
Keywords: Aspiration pneumonia; intoxication; gastric lavage; activated charcoal; GLASGOW COMA SCALE